Relationship between Personality Characteristics and Sleep Quality in Menopausal Women: A Comprehensive Review - Radeah Mohammed Alnasser et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Menopause is a critical phase in a woman's life characterized by physiological, hormonal, and psychological changes that can significantly affect sleep quality. Personality traits, such as neuroticism, extraversion, and conscientiousness, play an essential role in determining how women cope with menopausal symptoms, including sleep disturbances. This review examines the relationship between personality characteristics and sleep quality in menopausal women, highlighting key findings from recent studies. Furthermore, the implications for targeted interventions to improve sleep quality are discussed. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/278 https://doi.org/10.5281/zenodo.14481061